Bad optics : a Woods cop mystery - Heywood, Joseph (Heywood, Joseph. Woods cop mystery, 2018)
"In the eleventh Woods Cop Mystery, Conservation Officer Grady Service is on unpaid suspension but continues to voluntarily patrol the Mosquito Wilderness. He senses political shenanigans-an old foe lurking in the shadows and it seems someone wants to illegally commercialize the Mosquito. Grady realizes if he doesn't stop it, the wilderness will be destroyed. The tight story unfolds like a poker game, with one side bluffing and raising, while the other side keeps calling and keeping the game on until there is a final showdown"--Provided by publsiher.